The effect of giving moringa tempeh flour on hemoglobin levels and body weight of Wistar Rats - Cucuk Suprihartini; Arya Ulilalbab; Frenky Arif Budiman (Jurnal SAGO Gizi dan Kesehatan, 2023)
Background: Tempeh is a fermented product that has earned the nickname "the miracle food" because of its nutritional content, especially amino acids and fatty acids, which are good for health. Moringa leaves, which are also called "the miracle leaves," have complete nutritional content, especially iron, and vitamin C. Vitamin C plays a significant role in the absorption and metabolism of ironObjectives: Was to increase absorption of iron, which can increase hemoglobin blood and body weight  of ratsMethods: There were 4 groups, each consisting of 6 rats. The rats were kept in animal laboratories at room temperature (25–27°C) for 21 days. This research was conducted from 7 to 27 October 2020 in the Pharmacology Laboratory of Medicine, Faculty of Medicine Universitas Muhammadiyah Malang. This study used a Completely Randomized Design, used 24 Rattus norvegicus with treatment conditioned with anemia. The four groups were divided into control anemia rats, control non-anemia rats, anemia rats that consumed tempeh, and anemia rats that consumed tempeh with moringa leaves of 4%. The rats body weight was weighed daily and the blood Hb was taken at the end of the treatment. Statistical test used One-way Analysis of Variance (α = 0,01).Results: The results of statistical tests with ANOVA show not significant influence. The results of the hemoglobin and body weight rats had no significant effect.Conclusion: The value was not significant between groups in the hemoglobin assessment, but the treatment group that was given moringa leaves tempeh was higher than the anemia control group and the pure tempeh group.